(3eaJGM GdNjQ aj TQM OjHGLI QSGdI GdWjQs - (3Ydj Hf SdjeGf GdHMQGfis; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s ((3eMeO Hf GdTjN WGgQ GdSeGhi s)
(3ChdgG (B:s
(3hHYO abO JUaMJ OjHGLI GdQSGdI GdeSeGI HQSGdI GdWjQ s
(3BNQgG (B:s
(3hdcf GcKQge ddMb cGQghf QHfG GNQLfG efgG aEfG WGZhf s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B524 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B877s
Keywords: (3GdadSaI hGdefWbs